2018 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2018
DOI: 10.1109/robio.2018.8664812
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Rehabilitation System Based on SSVEP Brain-Computer Interface for Upper Extremity

Abstract: Traditional rehabilitation therapies have limited effect on the motor recovery for a tetraplegia patient. Brain-computer interface (BCI) systems allow patients to send commands or intents to control external devices without depending on the normal way of peripheral nerves and muscles. And hence it can provide an alternative control and communication method with a potential to replace, restore, even reinforce lost movement ability for individuals with neurological damages. In the study, we proposed a robot-assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The advantages and disadvantages of each of them depend on the signal and the application. A simple and efficient ML algorithm, LDA, was among the best methods in terms of classification accuracy and ITR used in P300-based (ACC = 100% orthosis) ( Stan et al, 2015 ) (ACC = 94.3%) ( Duvinage et al, 2012 ), and SSVEP-based BCI systems selected in the SLR (ACC = 79%, ITR = 27.54 bpm-FES) ( Zhao et al, 2016 ), (ACC = 83.33%, ITR = 1.55 bpm -VR) ( Tidoni et al, 2017 ) (ACC = 82.22% -FES) ( Yao et al, 2011 ), (ACC = 80-96% -FES) ( Yao et al, 2012 ), (ACC = 82.30%, ITR = 27.4 bpm) ( Chu et al, 2018 ) (ACC = 92.4%) ( Gui et al, 2015 ), (ACC = 85% -FES) ( Ding-Guo and Ying, 2012 ). Moreover, classification Accuracy obtained with LDA in P300-based BCI is slightly higher than with SSVEP-based BCI.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages and disadvantages of each of them depend on the signal and the application. A simple and efficient ML algorithm, LDA, was among the best methods in terms of classification accuracy and ITR used in P300-based (ACC = 100% orthosis) ( Stan et al, 2015 ) (ACC = 94.3%) ( Duvinage et al, 2012 ), and SSVEP-based BCI systems selected in the SLR (ACC = 79%, ITR = 27.54 bpm-FES) ( Zhao et al, 2016 ), (ACC = 83.33%, ITR = 1.55 bpm -VR) ( Tidoni et al, 2017 ) (ACC = 82.22% -FES) ( Yao et al, 2011 ), (ACC = 80-96% -FES) ( Yao et al, 2012 ), (ACC = 82.30%, ITR = 27.4 bpm) ( Chu et al, 2018 ) (ACC = 92.4%) ( Gui et al, 2015 ), (ACC = 85% -FES) ( Ding-Guo and Ying, 2012 ). Moreover, classification Accuracy obtained with LDA in P300-based BCI is slightly higher than with SSVEP-based BCI.…”
Section: Discussionmentioning
confidence: 99%
“…Such motor impairments negatively affect their independent living, including performing activities of daily life [33,85]. Rehabilitation therapies are commonly adopted to help people with motor impairment regain strength and control over their impaired body parts and may help them fully or partially restore their motor ability [10]. Performing rehabilitation exercises in a hospital is a common step that many people with motor impairments (e.g., stroke survivors) take when following rehabilitation therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, achieving success in these interventions requires a substantial commitment of time and effort. Numerous studies have demonstrated that the use of efficacious therapeutic methodologies can yield noteworthy enhancements in the patient’s state, notably in select instances of disorders of the nervous system [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study indicated an average accuracy of 65.89% in the BCI, based on the analysis of 10 subjects. The study conducted by the authors in reference [ 3 ] employs a similar paradigm to regulate a basic exoskeleton designed for arm rehabilitation. The system operates using three distinct control frequencies, namely, 12 Hz, 15 Hz, and 20 Hz.…”
Section: Introductionmentioning
confidence: 99%